Design and experiment of high-speed straw cleaning unit with double air springs - Xia, Xiaomeng; Li, Honggang; Liu, Shuyan; Ran, Ruiqiang; Cong, Yongjian; Jin, Yuhan; Huang, Dongyan (International Journal of Agricultural and Biological Engineering, 2024)
No-tillage planters need to be equipped with row cleaners to remove post-harvest plant residue from the seedbed. The two-disc row cleaners cannot effectively remove the plant residue at high speed because the working depth is unstable, which leads to poor seeding quality of the seeder. A straw cleaning unit with double air springs was designed to achieve better straw cleaning performance at high speeds. The analysis of the mechanical characteristics of the double air spring system showed that it enabled separate adjustment of force and stiffness. A dynamic model of the straw cleaning unit was established, and the effectiveness of the double air spring system with adjustable stiffness in stabilizing the working depth of the row cleaners was analyzed. Field experiments were conducted to evaluate the straw cleaning performance and consistency of downforce against the ground of the straw cleaning unit with double air springs at different high speeds. The results showed that the stiffness of the double air spring system for better straw cleaning performance of the straw cleaning unit was different at different working speed, and the required stiffness increased as the working speed increased; When the working speed was 8-12 km/h, the coefficient of variation of cleaned strip width was 6.9%-12.1%, the straw cleaning rate was 81.6%-92.2% and the root mean square error of downforce was 19.93-28.63 N; the coefficient of variation of cleaned strip width was moderately positively correlated with the root mean square error of downforce, and the cleaned strip width consistency was better when the root mean square error of downforce was lower than 25.00 N. Key words: conservation tillage; row cleaners; straw cleaning unit; double air spring system DOI: 10.25165/j.ijabe.20241704.8245 Citation: Xia X M, Li H G, Liu S Y, Ran R Q, Cong Y J, Jin Y H, et al. Design and experiment of high-speed straw cleaning unit with double air springs. Int J Agric & Biol Eng, 2024; 17(4): 89–97.